The Role of Local Government in Preventing Drug Abuse: A Legal Pluralism Approach - Oktavia, Susanti; Ari Atu Dewi, Anak Agung Istri (Westscience Press, 2025)
Drug abuse is a serious problem that requires attention and collaborative action from various parties, including the government, social institutions, and the community, especially the Traditional Village. This study aims to explore the role of the Bali Provincial Government and Traditional Villages in efforts to prevent and eradicate drug abuse. The research method used is normative law with a legislative approach and qualitative analysis. The results of the study indicate that the Bali Provincial Government has implemented various programs, such as collaboration with the National Narcotics Agency (BNN), socialization to the community, strengthening regulations, and providing rehabilitation facilities for drug users. In addition, Traditional Villages play an important role in educating the community about the dangers of drugs, forming anti-drug cadres, and providing social support for individuals at risk. Cooperation between Traditional Villages and the government, as well as a cultural-based approach, are key to creating a safe and drug-free environment. This study emphasizes the importance of collaboration between the government, institutions, and the community in overcoming drug abuse in Bali, in order to create a healthy society that is free from the dangers of drugs.